Features of bacterial growth and polysaccharide production of Streptococcus pneumoniae serotype 14 - Massaldi, Hugo Alberto (2010)
The effect of several cultivation conditions on the kinetics of bacterial growth and polysaccharide production of Streptococcus pneumoniae serotype 14 was studied. The presence in the supernatant of serotype-specific CPS (capsular polysaccharide) during growth was followed by size-exclusion HPLC and, in parallel, confirmed by using a specific latex reagent. The agitation level did not affect the production behaviour, whereas pH maintenance above 6 strongly enhanced both growth and CPS production throughout the cultivation period in flasks. Production of high-molecular-mass polysaccharide was found to be maximal between 5 and 6 h of cultivation, at the end of the exponential phase. By laser light scattering, 90% of this purified CPS product showed a Mw (molecular mass) range from 350 to 1500 kDa, with an average Mw of 921 kDa. Extending the culture to 24 h gave rise to a clear shift of the Mw distribution of the polysaccharide to values lower than 100 kDa. These findings may have strong implications for the large-scale manufacture of the polysaccharide and the associated conjugate vaccine.